Why Muslims should Maintain their Dignity in Worldly Life: A Critical Consideration on Said Nursi’s Insight on the Meaning of “Theology of Hope” as Reflected in His Damascus Sermon - Fauzan Saleh (Sunan Kalijaga: International Journal of Islamic Civilization, 2018)
“At one time Muslim culture led the world in knowledge and prosperity. Now, in most respect, it lags far behind. What are the factors that led to its rise and subsequent fall?” (Perkins, 2003). Muslims fell under the Western domination for many centuries. As a result, they have lost their authority to administer their own matters independently. Whereas Muslims believe that they should attain worldly contentment and after life happiness altogether, in reality, they gain only a modest attainment to improve their prosperity and accordingly lose their political as well as cultural dignity. They have been overshadowed by the West in many aspects of political and cultural affairs. But what made the West prosperous and triumphant over Muslim nations in general? To some extent, as one might believe, it is because they have adopted “prosperity theology.” While the term itself is controversial among Christian theologians, the issue has roused a profound awareness among Western people about the importance of personal empowerment, proposing that it is God’s will for humans to live prosperously. What did Nursi say about the necessity of cultivating prosperous life in Islam and what did he say about the demand to maintain dignity in this worldly life? This article tries to examine Nursi’s idea on the necessity of gaining worldly prosperity for advancing Muslim civilization as well as of maintaining their dignity by examining his insights on the “theology of hope” as reflected in his “Damascus Sermon” and other works compiled in his voluminous Risalei Nur.